Rupture properties of the 2020 Mw 6.8 Calama (northern Chile) intraslab earthquake. Comparison with similar intraslab events in the region. Issue 3 (3rd November 2022) - Herrera, Carlos; Pastén-Araya, Francisco; Cabrera, Leoncio; Potin, Bertrand; Rivera, Efraín; Ruiz, Sergio; Madariaga, Raúl; Contreras-Reyes, Eduardo
SUMMARY: We study the 2020 M w 6.8 Calama earthquake sequence that occurred within the subducting oceanic Nazca plate. The main shock is modelled via waveform inversion using a dynamic rupture model, while detection and location techniques are used to better characterize its aftershock sequence. We analyse the local seismotectonic and thermal context of the subducting Nazca plate to understand the trigger mechanism of this earthquake and how it compares with other significant earthquakes in the vicinity. The stress drop and the related dynamic rupture parameters of the Calama main shock are similar to those of the nearby 2007 M w 6.8 Michilla and 2015 M w 6.7 Jujuy intraslab earthquakes, which occurred to the west (trenchwards) and to the east (under the backarc) of the Calama earthquake, respectively. The sequences of these three events were located using a 3-D tomographic velocity model. While the Michilla earthquake sequence occurred within the oceanic crust at temperatures of ∼250 °C, the Calama sequence occurred within the upper lithospheric mantle at ∼350 °C and exhibited a smaller aftershock productivity than Michilla. Additionally, the 3-D tomographic model shows intermediate VP / VS ratios (1.72–1.76) in the region of the Calama earthquake. This indicates a less hydrated environment that could be responsible for the smaller aftershock productivity of the Calama earthquake.